PRELIMINARY CHARACTERISATION OF THREE FILIPENDULA SPECIES AS A POSSIBLE SOURCE FOR NUTRACEUTICALS - PukalskienÄ—, M.; Venskutonis, P. R. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Filipendula is a genus of 12 species of perennial herbaceous flowering plants in the family Rosaceae, native to the temperate regions of the Northern Hemisphere. The aim of this study was to determine essential oil composition and extract radical scavenging properties of the three species: European meadowsweet (F. ulmaria), dropwort (F. vulgaris), and Siberian meadowsweet (F. palmata). The plants have been used both for medicinal and food purposes; however publications on their biological properties and essential oil composition are rather scarce. The plants were subjected to the subsequent extractions with hexane, ethyl acetate, acetonitrile, methanol and water, i.e. in order of increasing solvent polarity. The radical scavenging capacity (RSC) was expressed as the EC50 value, which is defined as the amount of antioxidant necessary to decrease the initial concentration of a stable free radical DPPH by 50%. The highest RSC possessed methanol extracts followed by acetonitrile, ethyl acetate and water extracts. The RSC of hexane extract was negligible. The EC50 values of F. ulmaria, F. palmata and F. vulgaris methanol extracts were 0.21 mg/ml, 0.21 mg/ml, and 0.38 mg/ml, respectively. The extracts were analyzed by HPLC/MS and the differences in their composition were clearly observed. The essential oils were isolated by hydrodistillation, analyzed by GC/MS and the differences between the studied species were evaluated. Preliminary results show that Filipendula species are promising plants for expanding their uses, however further studies are needed to determine most valuable bioactive components and to assess the feasibility of their commercial cultivation and processing.